A novel diffusion flux modeling for laminar premixed flame simulation with OpenFOAM - Kamma P. (2023)
In this study, we developed a mass diffusion coefficient model for premixed combustion to reduce the computational time, in mixture-averaged diffusivities to serve as a microcomputer resource. In the development, a preliminary theory was derived to construct the associated variables and corrected using a benchmark model as the mixture-averaged model based on Chapman–Enskog binary diffusion. In the validation, the calculation results obtained using the proposed model with a benchmark case, regardless of thermal diffusion and for several fuels at various pressures, temperatures, and initial mixture compositions, showed good agreement. Validation was also performed with the two-dimensional premixed and partially premixed combustion models by implementing the novel diffusion coefficient model in OpenFOAM software. The OpenFOAM solver results were in good agreement with the experimental results. This solver showed good simulation performance at both micro and macro scales. In addition, the processing time was reduced by approximately 70% in all the simulated premixed flame models. Based on these findings, we conclude that the developed model allows researchers to work with more complex premixed combustion modeling with less computational time.